Transiting cassava into an urban food and industrial commodity through agroprocessing and marketing driven approaches: lessons from Africa - Abass, A.; Bokanga, M.; Dixon, A.; Bramel-Cox, P.J. (2009)
The International Institute of Tropical Agriculture (IITA), in partnership with African institutions, is testing a research for development (R4D) approach to develop cassava productivity and agro-industry to reduce poverty and hunger in Africa. During the research phase (1983–1995), agro-processing technologies for making intermediate cassava products such as high quality cassava flour (HQCF) were developed for industrial applications and for making ready-to-eat urban foods. These were tested at a pilot scale with farmers and food factories in West Africa (1995–1998). The technologies were transferred across 25 African countries (1996–2001). Nigeria advanced to the industrial phase in 2005; the private sector established several cassava-based agro-processing plants. Increase in demand for cassava from the agro-processing plants led to an increase in farm-gate prices, farm sizes, cassava yields, and total production of cassava in Nigeria. Meanwhile, the combined activities of national and international research centers, multilateral development institutions and NGOs had some influence in the cassava transformation process in East and Southern African countries. This paper reviews the key elements that influenced the transition in Nigeria, and proposes an approach to jump-start agro-industrial development, improve food security, and reduce hunger in Africa.